Prevalence and determinants of effective breastfeeding technique among early postpartum mothers in Fuzhou, China: A cross-sectional study - Neema E. Mawi; Hu Rong-Fang; Heavenlight A. Paulo; Na Chen; Gui-Hua Liu; Mohammed Abba-Aji (PLoS ONE, 2025)
Background Breastfeeding technique (BFT) is determined by the mother’s and infant’s positioning, the infant’s attachment to the breast, and the infant’s suckling behavior. Understanding breastfeeding mothers’ skills is crucial for clinical practice and for designing interventions to improve breastfeeding practices. This study aimed to determine the prevalence and determinants of effective BFT among early post-partum mothers. Methods We conducted a cross-sectional study among 415 early post-partum mothers in Fuzhou, China. Participants were recruited using a systematic random sampling technique. Data were collected using a self-administered questionnaire and a standardized observational checklist (WHO B-R-E-A-S-T Feed observation form). Descriptive statistics were used to assess the prevalence of effective BFT, and logistic regression was applied to identify its determinants. Results The overall prevalence of effective BFT was 70.4%. After adjusting for potential confounders, the prevalence ratio (PR) of effective BFT was greater among participants with college (PR = 1.20) and postgraduate education (PR = 1.41) compared to those with a technical education or lower. Participants who attended antenatal care (ANC) (PR = 1.04) and those with BFT knowledge (PR = 1.37) were more likely to practice effective BFT compared to participants who did not attend ANC and without such knowledge respectively. Similarly, those who received BFT counseling during pregnancy or immediately after delivery were 25% and 30%, respectively, more likely to practice effective EBT than those who did not. Conversely, experiencing breast problems was associated with a 42% lower likelihood of practicing effective BFT than those without breast problems. Conclusion Effective BFT is prevalent among early postpartum mothers in Fuzhou, China, with education level, antenatal care attendance, knowledge, and counseling playing significant roles in its practice. Efforts to improve breastfeeding outcomes should focus on enhancing educational interventions and providing targeted counseling during pregnancy and the immediate postpartum period, while addressing breast health issues to mitigate their impact on breastfeeding effectiveness.